2014
DOI: 10.6007/ijarbss/v4-i9/1178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organizational Characteristics on Employees’ Workplace Preferences

Abstract: The purpose of this study is to find the important attributes of organizations that effect employee choice, using conjoint analysis as an analytical tool. According to the purpose firstly 11 organizational attributes were determined based on relevant literature then the following five attributes of organizations were identified with a pilot study: pay level, social insurance, organizational reputation, working hours and transportation. Using subjects from a cement factory in Ordu, 105 respondents were asked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This is somewhat surprising given that the literature establishes a high relevance of pay for the promotion of favorable work-related outcomes in emerging countries (e.g. Adigun and Stephenson, 1992; Chiu et al , 2002; Yigit et al , 2014; Yucelt, 1982). Accordingly, our findings put a question mark over the frequently encountered assumption that Chinese workers are solely guided by a “cash mentality” (Luk and Chiu, 1998) and that “monetary incentives are the most effective motivational tools for getting Chinese workers’ commitment and getting them to improve their performance” (Ahmad, 2001, p. 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is somewhat surprising given that the literature establishes a high relevance of pay for the promotion of favorable work-related outcomes in emerging countries (e.g. Adigun and Stephenson, 1992; Chiu et al , 2002; Yigit et al , 2014; Yucelt, 1982). Accordingly, our findings put a question mark over the frequently encountered assumption that Chinese workers are solely guided by a “cash mentality” (Luk and Chiu, 1998) and that “monetary incentives are the most effective motivational tools for getting Chinese workers’ commitment and getting them to improve their performance” (Ahmad, 2001, p. 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Balabanova et al ’s (2016) finding revealed that wage satisfaction was the strongest negative predictor of Russian blue-collar workers’ intentions to leave. Finally, the analysis by Yigit et al (2014) demonstrated that high wages were the most important factor in blue-collar workers’ employer choices in Turkey.…”
Section: Research Background and Hypotheses Developmentmentioning
confidence: 96%